Scarodytes hindiluva sp. nov. from eastern Türkiye (Coleoptera, Dytiscidae, Hydroporini) - Aykut Medeni̇; Tusun Sadreddi̇n; Fery, Hans (Zootaxa, 2026)
Scarodytes hindiluva sp. nov. is described from the Hındıluva plateau in Mardin province and the Tapantepe region in Bingöl province, both in eastern Türkiye. Together with the new species the genus Scarodytes Gozis, 1914 includes now 14 species and one subspecies. The habitus, the male and female genitalia as well as the variation of several morphological characters of the new species are illustrated. The species is compared in detail with the three species of the genus previously recorded from Türkiye.